2010
DOI: 10.1359/jbmr.090829
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide expression analyses establish dendritic cells as a new osteoclast precursor able to generate bone-resorbing cells more efficiently than monocytes

Abstract: Dendritic cells (DCs), mononuclear cells that initiate immune responses, and osteoclasts (OCs), multinucleated bone-resorbing cells, are hematopoietic cells derived from monocytic precursor cells. Using in vitro generated dendritic cells, we previously showed that human and murine DCs could transdifferentiate into resorbing osteoclasts in the presence of macrophage colony-stimulating factor (M-CSF) and receptor activator of NF-kB ligand (RANKL). In this study we globally compared by transcriptomic profiling th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 46 publications
2
50
0
1
Order By: Relevance
“…Osteoclasts express several markers, such as TRAP, CALCR and CFMS throughout the differentiation process which, along with multinucleation and resorption, characterize the osteoclast phenotype [47]. CALCR is expressed on the surface of mature osteoclast and it has been described as the best differentiation marker for the osteoclast [48].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclasts express several markers, such as TRAP, CALCR and CFMS throughout the differentiation process which, along with multinucleation and resorption, characterize the osteoclast phenotype [47]. CALCR is expressed on the surface of mature osteoclast and it has been described as the best differentiation marker for the osteoclast [48].…”
Section: Discussionmentioning
confidence: 99%
“…We used osteoclastogenesis expression data (available from the ArrayExpress database under accession number E-MEXP-2019) on 0, 5, and 20 days [32]. Our analysis showed that most changes occurred within the first 5 days, since the expression changes between 0 and 5 days were very similar to those observed between 0 and 20 days, and very few genes changed between 5 and 20 days (Figure 2A and Additional file 6).…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, all the data so far obtained have described wide osteoclastogenic plasticity across the myeloid lineage of which very early myeloid precursors as well as committed Mo, macrophages, and DCs can differentiate into OCs. [11][12][13][14][15][16][17] It is now established that M-CSF induces GMPs or GMPderived cells to differentiate into OCs precursors that express RANK, the receptor of RANKL, and Triggering receptor expressed by myeloid cells-2 (TREM2). 18,19 Upon recognition of RANKL by RANK and activation of Immunoreceptor tyrosinebased activation motif (ITAM) family receptors, OC precursors undergo further differentiation to mononuclear pre-OCs with a high activity of the transcription factor Nuclear factor of activated T cells, cytoplasmic 1 (NFATc1), and a high expression of resorption-related genes, e.g.…”
Section: Osteoclasts Are Multinucleated Cells From the Monocytic Lineagementioning
confidence: 99%